Don’t forget the pediatric intensive care units: the nurses’ point of view - Emanuele Buccione; Michele Stellabotte (Infermieristica Journal, 2024)
Currently, in Italy, there are not enough paediatric intensive care beds, and an adequate number of trained nurses is lacking, particularly in paediatric settings. This could result in decreased quality of care and safety levels for patients and their families.